Reforma agrária no Brasil: uma contribuição ao debate - Teixeira, Paulo Henrique Rangel (1999)
This work starts from two hypotheses: that agrarian reform is still a prerequisite for development and, as a second hypothesis, agrarian reform has not yet been done in the country. In search of proof of these hypotheses, the work was divided in two, in the first part and a theoretical discussion was made to draw attention to the fact that the debate that is taking place in Brazil underestimates the objectives and justifications of agrarian reform. The debate is recovered and some views on the role of land reform are put forward, allowing us to identify that, due to the authors' conception of development, land reform is no longer seen as a prerequisite for development. Through the recovery of the debate on agrarian reform in Brazil, we identified that: Of the existing proposals in the 60s, the Peasant Reform and the Bourgeois Reform, the latter was the one that “won”, thus decreeing the end of the possibility of breaking with the patrimonialist landowning power. In the 80s and 90s, because it did not break with the concept of development as a synonym for industrialization, it is no longer possible to see Agrarian Reform as a prerequisite for development. This being only a way to compensate for the social problems caused by the Conservative Modernization of Brazilian agrarian. We present the concept of Human Development, which brings new elements to discuss the development process, such as growth with equality and the political participation of citizens. We adopted this development paradigm, which breaks with the understanding of development as a synonym for industrialization, and allows us to incorporate new variables, to raise some relevant points for the debate on land reform. Based on new studies that affirm that the initial land distribution is a determining variable for economic growth to occur, we conclude that it becomes a prerequisite for development since it promotes distribution and, consequently, growth. However, we realize that the simple distribution of land is not enough to provide the basis for long-term development. For the case of Brazil, in which the economic power arising from land tenure was reflected in a backward political power structure that continues over time, the breakdown of agrarian political power through the penalization of the latifundium and the resulting political participation these are elements without which it will not be possible to carry out our development process. In this way, agrarian reform as a prerequisite for development can only be conceived if it is proposed as a mechanism to solve the great structural problem of our historical formation, the concentration of the population. property and the forms of political power related to it. In the second part, the public action plans in the agrarian sphere from 1985 to 1998 are analyzed. In this part we try to understand how the different governments dealt with the agrarian issue. The analysis of the ways in which the agrarian reform policy in Brazil has been conceived and mainly implemented during the mentioned period, provides subsidies for the discussion of the political dimension of the theme and for the verification of the second hypothesis of work raised, there was no reform Agrarian that changed the structure of rural patrimonial power in the country. When we analyzed the elaborations of the agrarian reform proposals of the different governments, we found that they were always thought of as compensatory social policy, although the main objective was to appease conflicts in the countryside. In the third part, when we present the results of these Policies focused on the agrarian issue and analyze the living and social conditions of the settlements, as well as their economic and productive situation, we were able to complement and reinforce the proof of the hypothesis that the debate on Agrarian Reform it's out of focus. We found that the projects were relatively successful in the productive and economic aspects. In other words, the result of governmental interventions in the Brazilian agrarian sector has met the objectives demanded by the authors analyzed in this work, as they generated employment and income, avoided rural exodus, created a stock of social capital, modified the bases of local power, made it possible the insertion of beneficiaries in the market as commercial producers, and promoted the subsistence of families. This ends up restricting the debate to a question of quantity and speed of the settlement policy, or rather, of the Land Policy, losing the debate on the modification of the Brazilian Agrarian. In the conception that we are seeking to rescue from Agrarian Reform, that is, to modify the patrimonial structure and break with the political power coming from the land, what happened in the national Agrarian was not a Reformation. We also call attention to the “distribution” of land that is being carried out under the current government (the largest in the history of the country), which has an interesting characteristic, does not penalize the landowner and, in a way, meets the new demands of the segment of agrarian elites, bearing in mind that the price of land is low and new business opportunities arise, mainly related to media power. We emphasize that a patrimonial repositioning may be taking place, leading agrarian elites to look for other more profitable assets that allow the maintenance of the monopoly of power, other than land. This fact has been called a “silent revolution”. Finally, we emphasize that losing the political dimension of the debate in the case of land reform is very dangerous. The land issue has to do with the monopolization of political power and its effects on democratization and the political participation of rural citizens in the development process. As land transfer from landowners to landless has been done, it is not breaking with the backward political power that is a structural factor that inhibits development. Carry out agrarian reform and promote a greater distribution of land assets and, above all, break the political power of the landowner. It is breaking with two structural problems of our society, the concentration of property and the monopolization of the political patrimonial power. This is the real role of land reform in development, that is, a mechanism for solving one of our biggest structural problems.